DISSOCIATIVE TRANCE DISORDER MECHANISM AMONG UNIVERSITY STUDENTS - Novita Ayu Nafisa Rachman; Pambudi Rahardjo (PSIMPHONI, 2021)
This research aims to examine the mechanism of dissociative trance disorder among university students in Purwokerto. The research focuses on the mechanism of dissociative trance disorder among university students in Purwokerto. The research method is qualitative with a case study approach. There are 4 participants and 4 secondary informants in this research. Those who have experienced dissociative trance disorder become primary informants while those who have close relationships with the primary informants become secondary informants. The data were analyzed by using an interactive model, involving data collection, data reduction, data display, and drawing a conclusion. The research result revealed that there are 4 informants who go through the mechanism in the process of dissociative trance disorder occurrence. The mechanism includes four stages, namely the physical symptoms stage, the pre-loss of consciousness stage, the loss of consciousness stage, and the conscious stage.